Implementation of the Guidance and Counseling Services Principles in Mathematics Learning - Sutirna, Sutirna; Musa, Safuri; Suprananto, Suprananto; Intisari, Intisari (FKIP Universitas Lampung, 2023)
This study aims to provide information about the effect of implementing the principles of guidance and counseling services in mathematics learning as a solution to low mathematics learning outcomes. The instruments used include a written test in the form of multiple choices. The results of the study were strengthened by the results of student interviews and learning observation assessment sheets by mathematics teachers as observers. The results showed that the simple linear regression equation test, namely Y = 2.019 + 0.901 X, showed a positive direction. Therefore, the treatment has a significant effect on student learning outcomes as indicated by the percentage increase in learning outcomes of 58.48% from the difference between the average pretest and posttest scores.Keywords: principles of guidance and counseling services, mathematics learning, mathematics teachers.DOI: http://dx.doi.org/10.23960/jpmipa/v24i1.pp135-151